Combination of Quercetin or/and siRNA-loaded DDAB-mPEG-PCL hybrid nanoparticles reverse resistance to Regorafenib in colon cancer cells - Shabnam Shahidi; Kobra Rostamizadeh; Mojtaba Fathi; Keivan Nedaei; Ali Ramazani (BMC, 2022)
Abstract Background Colorectal cancer (CRC) is the second leading cause of cancer death. Although Regorafenib showed survival benefits in patients with CRC, reports imply the recurrence of malignant phenotype resulting from chemotherapy. Evidence demonstrated that a5β1 integrin plays an important role in the Regorafenib treatment, which, may be led to resistance. In this study, the effects of /siRNA or/ and Quercetin loaded DDAB-mPEG-PCLnanoparticles could reverse this resistance phenotype in colon cancer cells in vitro. Methods Regorafenib-resistant Ls-180 colon cancer cell line was developed by long-term exposure to Regorafenib. Quercetin and Regorafenib were separately encapsulated into mPEG-PCL micelles through the nano-precipitation method and characterized by DLS. Optimized doses of Quercetin and Regorafenib were used for combination therapy of resistant cells followed cytotoxicity study using MTT. Gene expression levels of the β1 subunit of integrin were determined by the real-time method of RT-PCR. Results Developed Regorafenib resistant LS-180 showed to have Regorafenib IC50 of 38.96 ± 1.72 µM whereas IC50 in non-resistant cells were 8.51 ± 0.29 µM, which meaningful was lower statistically compared to that of a resistant one. The β1 mRNA level of whole α5β1 integrin was significantly higher in the resistant cells compared to those of non-resistant ones. Gene expression levels in each siRNA-loaded nanoparticle and Quercetin-loaded one were lower than that in mock experiments. Finally, when these two types of nanoparticles were used to treat resistant cells, gene expression decrease of integrin indicated a greater effect that could be capable of reverse resistancy. Conclusion Results of this study demonstrated another confirmation of involving integrins in cancer resistance following chemotherapy using Regorafenib. Also, it indicated how using siRNA targeting integrin could enhance the plant derivatives like Quercetin effects to reverse resistance in vitro.